The relationship of socio-demographic characteristics and knowledge of breast cancer on stage of behavioral adoption of breast self-examination - Moey, Soo Foon; Abdul Mutalib, Aaina Mardhiah; Che Mohamed, Norfariha; Saidin, Nursyahirah (AIMS Press, 2020)
Abstract: Background/aim: In Malaysia, breast cancer is the most common cancer among women. As such, early diagnosis and screening practices are important to increase the survival rate. Breast self-examination (BSE) is one of the main screening methods for breast cancer. Socio-demographic characteristics and knowledge of breast cancer are amongst the crucial roles in determining women’s behavioral adoption in performing BSE. This study aims to assess the relationship of socio-demographic factors and knowledge of breast cancer on the stage of behavioral adoption of BSE among Malaysian women in Kuantan, Pahang. Materials and methods: A cross-sectional study was conducted on 520 women from three different government health clinics in Kuantan and IIUM Family Health Clinic from February to April 2018. Data were collected using a self-administered questionnaire on socio-demographic factors and knowledge of breast cancer and its effect on the behavioral adoption of BSE. Results: Significant difference was found between socio-demographic characteristics and behavioral adoption of BSE. However, only breast screening and the best time for screening were found to be significant with the behavioral adoption of BSE and knowledge of breast cancer. Conclusion: It is found that most women in Kuantan, Pahang perform BSE but were still unaware of the importance of performing BSE for early breast cancer detection. This study was expected to enhance women's awareness of the benefits of performing BSE.